From Tibullus’s Palette of Literary Genres. Prayer and Religious Hymn as Exponents of the Poetic Program of the Elegiac Poet - Arndt, Aleksandra (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The article presents the analysis of hymns and prayers in the love elegies of Tibullus.